(3TQM bUjOI HGfJ SYGOs - (3dTGQM eLghds; (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s ((3YHO GdHGbi HQSe GdCejQ ejQRG eMehO NGf s)
(3ChdgG (B:s
(3HGfJ SYGO abdHi Gdjhe eJHhd eJje EKQgG de jaO ecHhd s
(3BNQgG (B:s
(3dG jbY GdWYf EdG ai fMhQge heGdge Yf MjGV GdehJ Jgdjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3fSNI KGdKIs
(3hHBNQgG JYbjHgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs